The New Orleans sniper : a phenomenological case study of constituting the other - Waksler, Frances Chaput (University Press of America, 2010)
On January 7, 1973, shots were fired from Howard Johnson's Motel in New Orleans, LA. Six were killed, ten wounded, and the debate began about the number of snipers. Waksler traces the course of this event and analyzes claims and counterclaims made in the search to explain it.